2014
DOI: 10.1177/0954405414526384
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into grindability of a superalloy and effects of grinding parameters on its surface integrity

Abstract: GH4169 is comparatively a new superalloy mainly used as turbine components because of its outstanding combination properties such as high-temperature strength, thermal stability and wear resistance. But these also make it hard to cut, and its machined surface quality and integrity are particularly sensitive to the manufacturing process employed. The existing researches on machining-induced surface integrity and machinability of hard-to-cut materials are briefly reviewed; the effects of processing parameters on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
1
15
0
4
Order By: Relevance
“…Likewise, Sunarto and Ichida [207] concluded that CBN-U was better suited for grinding applications requiring high dimensional accuracy. More recently, Zeng et al [247] showed that varying depths of cut (5-40 mm) had a significant influence on workpiece surface integrity when surface grinding GH4169 nickel based superalloy using a Al 2 O 3 wheel. Although surface residual stresses remained tensile ($700 as opposed to 1200 MPa), workpiece roughness decreased (to 0.284 from 0.896 mm Ra) with no indication of material cracking and minimal subsurface microstructural alteration ($3 mm) when operating at the lowest depth of cut of 5 mm, see Fig.…”
Section: Nickel Based Superalloysmentioning
confidence: 99%
“…Likewise, Sunarto and Ichida [207] concluded that CBN-U was better suited for grinding applications requiring high dimensional accuracy. More recently, Zeng et al [247] showed that varying depths of cut (5-40 mm) had a significant influence on workpiece surface integrity when surface grinding GH4169 nickel based superalloy using a Al 2 O 3 wheel. Although surface residual stresses remained tensile ($700 as opposed to 1200 MPa), workpiece roughness decreased (to 0.284 from 0.896 mm Ra) with no indication of material cracking and minimal subsurface microstructural alteration ($3 mm) when operating at the lowest depth of cut of 5 mm, see Fig.…”
Section: Nickel Based Superalloysmentioning
confidence: 99%
“…Z uwagi na te zjawiska autorzy prac dotyczących szlifowania stopów na osnowie niklu najczęściej rezygnują ze stosowania konwencjonalnych narzędzi ścier-nych na rzecz narzędzi wykonanych z materiałów supertwardych jak diament czy cBN. W swoich publikacjach opisują efekty procesu szlifowania z użyciem ściernic z materiałów supertwardych jak ściernice diamentowe oraz ściernice z regularnego azotku boru [7,8,9,10,11,12,13,14,15,16]. Zjawiska w strefie szlifowania W strefie szlifowania, w której narzędzie ścierne podczas pracy styka się z przedmiotem obrabianym, dochodzi do kontaktu czterech podstawowych elementów: ziaren ścier-nych, spoiwa, materiału obrabianego oraz środowiska.…”
Section: Szlifowanie Stopów Nikluunclassified
“…Zjawiska w strefie szlifowania W strefie szlifowania, w której narzędzie ścierne podczas pracy styka się z przedmiotem obrabianym, dochodzi do kontaktu czterech podstawowych elementów: ziaren ścier-nych, spoiwa, materiału obrabianego oraz środowiska. Kontakt tych elementów w warunkach wysokiej temperatury, wywołanej tarciem i dużą dynamiką procesu, może powodować zachodzenie reakcji chemicznych [17,18] -rys. 3.…”
Section: Szlifowanie Stopów Nikluunclassified
See 2 more Smart Citations